2017
DOI: 10.1016/j.celrep.2017.10.103
|View full text |Cite
|
Sign up to set email alerts
|

Impediment of Replication Forks by Long Non-coding RNA Provokes Chromosomal Rearrangements by Error-Prone Restart

Abstract: Summary Naturally stalled replication forks are considered to cause structurally abnormal chromosomes in tumor cells. However, underlying mechanisms remain speculative, as capturing naturally stalled forks has been a challenge. Here, we captured naturally stalled forks in tumor cells and delineated molecular processes underlying the structural evolution of circular mini-chromosomes (double minute chromosomes, DMs). Replication forks stalled on the DM by the co-directional collision with the transcription machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 67 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…While CDK inhibition prevents the initiation of DNA replication [ 32 ], the interaction of p21 with PCNA at replisomes would block the cell cycle after the initialization of the S phase. In such a scenario, strong reduction in the speed of nascent DNA elongation or its total inhibition would exacerbate the replication stress, a scenario that is not advantageous for the DDR [ 33 , 34 ]. Hence, the role of p21–PCNA interaction in the S phase must not necessarily parallel the model described for CDKs, in which the only effect caused by p21 when interacting with its partners is triggering their inhibition.…”
Section: Can Cell-cycle Arrest Be Achieved By P21–pcna Interactionmentioning
confidence: 99%
“…While CDK inhibition prevents the initiation of DNA replication [ 32 ], the interaction of p21 with PCNA at replisomes would block the cell cycle after the initialization of the S phase. In such a scenario, strong reduction in the speed of nascent DNA elongation or its total inhibition would exacerbate the replication stress, a scenario that is not advantageous for the DDR [ 33 , 34 ]. Hence, the role of p21–PCNA interaction in the S phase must not necessarily parallel the model described for CDKs, in which the only effect caused by p21 when interacting with its partners is triggering their inhibition.…”
Section: Can Cell-cycle Arrest Be Achieved By P21–pcna Interactionmentioning
confidence: 99%
“…In addition, promoter-associated RNA (pRNA) suppresses the expression of the rRNA genes by recruiting DNMT3b to the target site of TTF-I (a transcription factor) via complementarity with the rDNA promoter (Figure 2F) (80). Watanabe et al found that long non-coding RNA near the MYC gene could facilitate the amplification of MYC by influencing the movement of the replication fork (Figure 2E) (81). Another lncRNA known as ANRASSF1, produced from the opposite strand of a tumor-suppressor gene RASSF1 gene, binds with the promoter region of the parental gene, thus forming an RNA/DNA hybrid, and recruits polycomb repressive complex 2 protein (PRC2) to regulate its expression (82, 83).…”
Section: Future Perspectivementioning
confidence: 99%
“…Slow or arrested replication forks stimulate the use of potentially mutagenic DNA repair pathways that can lead to the accumulation of mutations and chromosomal rearrangements (reviewed in [ 8 , 9 ]). In addition, if the slow progression of replication cannot be compensated by the firing of dormant origins, there is the risk that cells will enter mitosis with unresolved replication intermediates ( Fig.…”
Section: Introductionmentioning
confidence: 99%